2014
DOI: 10.1155/2014/725361
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Drug Use among Chinese Men Who Have Sex with Men: A Risky Combination with Unprotected Sex for Acquiring HIV Infection

Abstract: Objective. To investigate the prevalence of recreational drug use and its relationship with HIV infection among Chinese MSM. Methods. A cross-sectional study of 625 MSM was conducted in Shenyang, China. Questionnaires were administered to collect information on recreational drug use and sexual behaviors. Blood specimens were collected to test for HIV and syphilis antibodies. Results. Nearly a quarter (23.2%, 145/625) of participants reported ever using recreational drugs, among which alkyl nitrites (poppers) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 25 publications
6
62
4
Order By: Relevance
“…This study, however, did not have a well-matched control group, and most of enrolled patients may have these bone disorders predate HIV infection and be caused by other risk factors such as drugs and alcohol consumption. Chinese high-risk population had lower usage rates of recreational drug and alcohol than developed countries [15,16], which may be the potential reason for this difference. Our result suggested that the patients in the early infection stage do not need to monitor BMD frequently, which is of less clinical significance and increases the economic burden of the patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study, however, did not have a well-matched control group, and most of enrolled patients may have these bone disorders predate HIV infection and be caused by other risk factors such as drugs and alcohol consumption. Chinese high-risk population had lower usage rates of recreational drug and alcohol than developed countries [15,16], which may be the potential reason for this difference. Our result suggested that the patients in the early infection stage do not need to monitor BMD frequently, which is of less clinical significance and increases the economic burden of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have found that the incidence of reduced BMD was higher in the MSM group [20,21]. Some traditional risk factors to reduce BMD such as smoking, alcohol, depression, poor nutritional status and recreational drug use were more likely to be prevalent among MSM [15,22], which may lead to the bone mass loss among them. Similar to these findings, our study revealed that MSM was independently associated with a 0.004 g/cm 2 (p = 0.017) lower BMD at femoral neck, after adjustment for demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a majority of countries, national drug surveillance systems do not collect or disaggregate data according to sexual orientation, meaning that estimates of drug use prevalence are largely reliant on community and clinical surveys of MSM. These are often subject to methodological limitations, including the lack of established sampling frame, limitations in the range of settings in which data is collected and varied time periods of reporting China, 23.2% had ever used recreational drugs, with the most common illicit substances being methylmorphine phosphate (5.1%), methamphetamine (4.0%) and ketamine (0.8%) (9). Evidence of drug use prevalence in the United States is hard to determine at a total population level due to state, city and sub-population sampling.…”
Section: Prevalence Of Drug Use Among Msmmentioning
confidence: 99%
“…Recreational drug use affects HIV transmission via several mechanisms, including physiological responses, routes of administration, venues at which drugs are used, incidence of HIV infection in specific drug-using populations, and cognitive effects on decision making [8]. Under the effect of recreational drugs, MSM may to have multiple sexual partnerships [9], participate in group sex[10], engage in condomless anal intercourse [11] and experience more intimate partner violence [12], which may further facilitate HIV transmission.…”
Section: Introductionmentioning
confidence: 99%